2020
DOI: 10.3389/fonc.2020.01341
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Wnt Ligands in Human Colorectal Cancer

Abstract: Colorectal cancer (CRC) is the fourth leading cause of cancer death worldwide, and constitutive activation of the Wnt signaling pathway is universal in most CRC cases. Wnt ligands (Wnts) are secreted glycoproteins and fundamentally essential for the transduction of Wnt signaling pathway. However, the 19 members of Wnts in humans imply a daunting complexity of Wnt signaling and biological effects, and our understanding of their roles in CRC tumorigenesis is still quite rudimentary. This review will give an over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 152 publications
(170 reference statements)
1
77
0
2
Order By: Relevance
“…We found that this pathway contains major Wnt ligands (Wnt5a, Wnt5b, Wnt6, Wnt10a, and Wnt10b) and the Wnt-upregulated genes (Adamts5, Bmp2, Bmp4, Itga3, Nfatc4, Ngf, Prkd3, and Sema3f) or downregulated genes (Mmp13, Pappa2, Prkd1, and Sema3e) (Fig. 5) (30)(31)(32)(33). Almost all of these Wnt ligands and Wnt-upregulated genes were upregulated in Colon 26 and all downregulated genes were downregulated in Colon 26 (Fig.…”
Section: Wnt Pathway Is Highlighted As One Of the Most Distinct Features Between Ct-26 And Colon 26mentioning
confidence: 91%
“…We found that this pathway contains major Wnt ligands (Wnt5a, Wnt5b, Wnt6, Wnt10a, and Wnt10b) and the Wnt-upregulated genes (Adamts5, Bmp2, Bmp4, Itga3, Nfatc4, Ngf, Prkd3, and Sema3f) or downregulated genes (Mmp13, Pappa2, Prkd1, and Sema3e) (Fig. 5) (30)(31)(32)(33). Almost all of these Wnt ligands and Wnt-upregulated genes were upregulated in Colon 26 and all downregulated genes were downregulated in Colon 26 (Fig.…”
Section: Wnt Pathway Is Highlighted As One Of the Most Distinct Features Between Ct-26 And Colon 26mentioning
confidence: 91%
“…Among them Wnt2b, Wnt3, Wnt3a, Wnt8a, Wnt8b, Wnt9a and Wnt10b mainly activate the canonical pathway, Wnt5b and Wnt11 activate the non‐canonical pathway, and Wnt1, Wnt2, Wnt4 Wnt5a, Wnt6, Wnt7a, Wnt7b, Wnt9b, Wnt10a and Wnt16 function as initiators for both signalling pathways. The structural characteristics and the maturation of all human Wnts have been elaborately summarized by our group and Kikuchi et al 19 , 30 However, the detailed mechanism by which single Wnt is chosen to produce and activate specific Wnt pathway has not been fully clarified. In the following parts, the exact role of each Wnt in the development of T2DM and related complications will be discussed separately (Table 1 ).…”
Section: Roles Of Wnts In T2dm and Related Complicationsmentioning
confidence: 99%
“…On treating HCT 116 cells with purified Wnt3a protein, we observed an increase in both protein and mRNA levels of CHIP along with an increased β-catenin protein level. Cyclin D1 was used as a positive control 37 for the pathway (Figure 2B). LiCl, a pharmacological inhibitor of GSK3β and known activator of βcatenin pathway 38 , was used to enhance Wnt signaling in HCT 116 and HT29 cells.…”
Section: Canonical Wnt Signaling Enhances Chip Expression In Colorectal Cancermentioning
confidence: 99%